Traffic Simulation–Based Learning to Foster Discipline and Academic Performance in Children - Husnul Qhatima; Pertiwi Kamariah Hasis (South Sulawesi Education Development (SSED), 2025)
Purpose: Discipline and academic achievement are essential foundations for children’s cognitive, moral, and behavioral development in early childhood education. However, many preschool children experience difficulties in internalizing rules and structured learning behaviors, particularly in classroom settings that lack experiential and engaging learning strategies. This study was conducted in response to these challenges and aims to examine the effectiveness of traffic simulation–based learning as an instructional strategy to improve discipline and academic achievement among preschool children. By integrating play-based simulation with rule-oriented activities, the study seeks to provide a contextually relevant pedagogical approach that supports both character formation and learning outcomes in early childhood education Methodology: This study employed a Classroom Action Research (CAR) design following the Kurt Lewin model, consisting of two cycles with four stages: planning, action, observation, and reflection. The participants were 12 children in Group B at Raudhatul Atfhal As’adiyah Pengkendekan during the 2021/2022 academic year. Data were collected through discipline observation checklists, learning outcome tests, and teacher activity observation sheets. The data were analyzed using descriptive quantitative analysis, focusing on percentage-based developmental criteria commonly used in early childhood assessment to evaluate changes across the pre-cycle, Cycle I, and Cycle II. Results : The findings reveal a consistent and significant improvement in both children’s discipline and academic achievement following the implementation of traffic simulation activities. Children’s discipline increased from 32% in the pre-cycle to 42% in Cycle I, and reached 83% in Cycle II, categorized as very well developed. Academic achievement also showed substantial improvement, rising from 49% in Cycle I to 84% in Cycle II. In addition, teacher instructional activity improved from 90% to 95%, indicating enhanced teaching effectiveness and classroom engagement during the intervention. Conclusions: The study concludes that traffic simulation–based learning is an effective pedagogical strategy for enhancing discipline and academic achievement in early childhood education. By providing concrete, experiential, and rule-based learning experiences, traffic simulation supports children’s self-regulation, understanding of social rules, and learning engagement. These findings contribute to early childhood education research by highlighting the value of simulation-based and play-oriented approaches as practical tools for integrating character education and academic development in preschool settings.